1997
DOI: 10.1126/science.276.5320.1868
|View full text |Cite
|
Sign up to set email alerts
|

Large Porous Particles for Pulmonary Drug Delivery

Abstract: A new type of inhalation aerosol, characterized by particles of small mass density and large size, permitted the highly efficient delivery of inhaled therapeutics into the systemic circulation. Particles with mass densities less than 0.4 gram per cubic centimeter and mean diameters exceeding 5 micrometers were inspired deep into the lungs and escaped the lungs' natural clearance mechanisms until the inhaled particles delivered their therapeutic payload. Inhalation of large porous insulin particles resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
613
0
11

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 1,092 publications
(638 citation statements)
references
References 19 publications
6
613
0
11
Order By: Relevance
“…Particles of 1-5 mm in diameter would likely be engulfed by antigen-presenting cells such as macrophages. 26,27 Edwards et al 28 have, however, demonstrated that larger, but very light particles permitted highly efficient delivery of inhaled particles into the systemic circulation. Thus particles with mass densities of o0.4 g/cm 3 and mean diameters exceeding 5 mm were inspired deep into the lungs and escaped the lungs' natural clearance mechanisms until the inhaled particles delivered their therapeutic contents.…”
Section: Discussionmentioning
confidence: 99%
“…Particles of 1-5 mm in diameter would likely be engulfed by antigen-presenting cells such as macrophages. 26,27 Edwards et al 28 have, however, demonstrated that larger, but very light particles permitted highly efficient delivery of inhaled particles into the systemic circulation. Thus particles with mass densities of o0.4 g/cm 3 and mean diameters exceeding 5 mm were inspired deep into the lungs and escaped the lungs' natural clearance mechanisms until the inhaled particles delivered their therapeutic contents.…”
Section: Discussionmentioning
confidence: 99%
“…[ 78 ] Insulin-loaded porous particles with diameter >5 µm and non-porous particles with diameter <5 µm, derived from the same polymer were compared. [ 78 ] Only porous particles were capable to maintain the high levels of insulin in the blood for more than 4 hours. The low clearance of the porous particles by phagocytic cells was also confi rmed.…”
Section: Sizementioning
confidence: 99%
“…In general, particles >10 mm will deposit in the upper airway, nanoparticles will be inhaled then exhaled, and particles with an aerodynamic diameter that is just right-perhaps 1-3 mm -will reach the small airways and alveoli (Edwards et al, 1998). However, larger porous particles can also be made to reach the lower airways (Edwards et al, 1997(Edwards et al, , 1998.…”
Section: Local Delivery For Local Therapymentioning
confidence: 99%